Fasciola hepatica in preschoolers of a town in a high Andean region of Peru - Fernádez-Holguín, Carlos (2023)
Introduction: Fasciola hepatica infection is a globally distributed, neglected and underdiagnosed zoonotic disease. Objectives: To determine the frequency of Fasciola hepatica infection among a preschool population in Tartar Chico, Baños del Inca, Cajamarca. Methods: Cross-sectional study in 48 children of an initial educational institution. Parents delivered 3 stool samples for the serial parasitological study and completed an epidemiological survey. The identification of F. hepatica and other parasites was carried out with the Lumbreras rapid sedimentation tests, direct examination, and Kato-Katz. For descriptive analysis, frequency and percentages were used, for the bivariate analysis, Chi-square or Fisher’s exact test was used. Results: The frequency of F. hepatica was 4,17%. In addition, a proportion of 8,33% of Ascaris lumbricoides, 4,17% of  Diphyllobothrium pacificum and 2,08% of hookworms; as well as contaminating parasites Entamoeba coli, Blastocystis hominis. Conclusions: A frequency of 4,17% of fascioliasis was found among preschoolers from a high Andean community in Peru.